2020
DOI: 10.1101/2020.02.15.950782
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oecophyllibacter saccharovoransgen. nov. sp. nov., a bacterial symbiont of the weaver antOecophylla smaragdina

Abstract: AbstractIn this study, bacterial strains Ha5T, Ta1 and Jb2 were isolated from different colonies of weaver ant Oecophylla smaragdina. They were distinguished as different strains based on matrix-assisted laser desorption ionization-time of flight (MALDI-TOF) mass spectrometry and distinctive random-amplified polymorphic DNA (RAPD) fingerprints. Cells of these bacterial strains were Gram-negative, rod-shaped, aerobic, non-motile, c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 71 publications
(76 reference statements)
0
3
0
Order By: Relevance
“…We found that, compared to a bacterial pathogen, a bacterial member of the Acetobacteraceae was not only better able to withstand acidic conditions created with formic acid in vitro but was able to establish itself in the midgut of formicine ants in vivo. This suggests that host filtering of microbes ( Mazel et al, 2018 ) via acidic crop lumens might explain at least part of the recurrent presence of Acetobacteraceae in the gut of formicine ants and the otherwise reduced microbial diversity and abundance of gut-associated microbes in formicine ants ( Brown and Wernegreen, 2016 ; Brown and Wernegreen, 2019 ; Chua et al, 2018 ; Chua et al, 2020 ; Ivens et al, 2018 ; Russell et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that, compared to a bacterial pathogen, a bacterial member of the Acetobacteraceae was not only better able to withstand acidic conditions created with formic acid in vitro but was able to establish itself in the midgut of formicine ants in vivo. This suggests that host filtering of microbes ( Mazel et al, 2018 ) via acidic crop lumens might explain at least part of the recurrent presence of Acetobacteraceae in the gut of formicine ants and the otherwise reduced microbial diversity and abundance of gut-associated microbes in formicine ants ( Brown and Wernegreen, 2016 ; Brown and Wernegreen, 2019 ; Chua et al, 2018 ; Chua et al, 2020 ; Ivens et al, 2018 ; Russell et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Though not formally established (see Mushegian and Ebert, 2016 ), recent studies indicate a mutualistic relationship between formicine ants, and their gut-associated Acetobacteraceae ( Brown and Wernegreen, 2019 ; Chua et al, 2020 ). Thus, the creation of an acidic crop environment in formicine ants that is easier to endure if colonizing microbes are mutualists agrees with the concept of screening as a mechanism to choose microbial partners out of a pool of environmental microbes ( Archetti et al, 2011a ; Archetti et al, 2011b ; Biedermann and Kaltenpoth, 2014 ; Scheuring and Yu, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation